Loss of thymic innate lymphoid cells leads to impaired thymopoiesis in experimental graft-versus-host disease - Dudakov, Jarrod A. (Blood, 2017)
Graft-versus-host disease (GVHD) and posttransplant immunodeficiency are frequently related complications of allogeneic hematopoietic transplantation. Alloreactive donor T cells can damage thymic epithelium, thus limiting new T-cell development. Although the thymus has a remarkable capacity to regenerate after injury, endogenous thymic regeneration is impaired in GVHD. The mechanisms leading to this regenerative failure are largely unknown. Here we demonstrate in experimental mouse models that GVHD results in depletion of intrathymic group 3 innate lymphoid cells (ILC3s) necessary for thymic regeneration. Loss of thymic ILC3s resulted in deficiency of intrathymic interleukin-22 (IL-22) compared with transplant recipients without GVHD, thereby inhibiting IL-22–mediated protection of thymic epithelial cells (TECs) and impairing recovery of thymopoiesis. Conversely, abrogating IL-21 receptor signaling in donor T cells and inhibiting the elimination of thymic ILCs improved thymopoiesis in an IL-22–dependent fashion. We found that the thymopoietic impairment in GVHD associated with loss of ILCs could be improved by restoration of IL-22 signaling. Despite uninhibited alloreactivity, exogenous IL-22 administration posttransplant resulted in increased recovery of thymopoiesis and development of new thymus-derived peripheral T cells. Our study highlights the role of innate immune function in thymic regeneration and restoration of adaptive immunity posttransplant. Manipulation of the ILC–IL-22–TEC axis may be useful for augmenting immune reconstitution after clinical hematopoietic transplantation and other settings of T-cell deficiency.